An intellectual history of British social policy idealism versus non-idealism - Offer, John 1949- (Policy Press, 2006)
The history of social policy is emerging as an area of growing interest to both students and researchers. This topical book charts the period from the 1830s to the present day, providing a fresh analysis of the relationship between social theory and social policy in the UK. Drawing on recent historical research, the book: · reconsiders and challenges many long-held beliefs about the 'evolution' of social policy; · presents a wide-ranging reappraisal of links between social theories and changes in social policy; · pays particular attention to the importance of idealist social thought as an intellectual framework for understanding the 'welfare state' ; · has a distinctive focus on the importance of ideas in the history of social policy
Title from publisher's bibliographic system (viewed on 18 Jan 2022)
Keywords: Geschichte 1830-2000; Public welfare / Great Britain / History; Sozialpolitik; Sozialphilosophie; Great Britain / Social policy; Großbritannien